(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the influence of different types of music in different age groups on the autonomic modulation of heart rate. Methods: 96 volunteers were obtained, 44 in the musical group - GM (24.6 years - 26 men and 18 women) and 52 in the non-musicalized group - GNM (23.9 years - 22 men and 30 women). Four different songs (M1, M2, M3 and M4) were played for 22 minutes preceded by a five-minute break. Data collection was performed by a heart rate monitor, POLAR brand, model RS800CX. Data analysis was performed in the time domain by the RMSSD and pNN50 indices, and in the frequency domain by the low frequency - LF (sympathetic activity), high frequency - HF (parasympathetic activity) and LF / HF (sympathetic-vagal balance) indices). Statistical tests were used for data analysis. Results: For the different age groups in the MG, variances were found between the young and middle-aged groups for RMSSD (during rest in M1 to M4), pNN50 (only at rest), HF (during rest, M1 and M2) and LF / HF (during rest, M1, M2 and M4), and adults compared to middle age at rest, M1 and M4. In GNM, differences were found related to GM (greater at rest in young people than middle-aged and greater in young people than adults and middle-aged during M1 and M3) and BF / HF (greater in young people compared to adults and a half age when performing M3 and M4). Conclusion: with advancing age, there is a reduction in the physiological indices of heart rate variability. In GM, this result is more evident, as young people in this group start from higher values ​​of parasympathetic activity index than in the GNM.